Countering Radicalism and Fundamentalism Through Cultural and Islamic Acculturation - Bedong, Muhammad Ali Rusdi; L, Sudirman (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
IAIN Parepare successfully countered radicalism and fundamentalism among the academic community through the vision of cultural acculturation and Islam, it can be seen with data and information during the vulnerable time of 2018-2021 not found the academic community reported to the campus code of ethics committee because of the issue of radicalism and fundamentalism, this can be successful because the recruitment pattern of students, lecturers, and employees emphasizes the value of religious moderation which is one of the indicators. It is accommodating to local culture.